Pengaruh Hard Skills dan Soft Skills terhadap Kesiapan Kerja Siswa di SMKN 10 Surabaya - Yaasmiin Hardyan Kota Assabul; Durinta Puspasari (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
The low level of student understanding regarding the importance of mastering hard skills and soft skills as the main capital in facing the world of work that continues to transform is a serious challenge in the world of vocational education. Amidst the rapid development of technology and changes in industrial needs, the world of work not only demands technical skills, but also good interpersonal and adaptive skills. The main objective of this study is to highlight the extent to which these two types of skills influence the work readiness of students at SMKN 10 Surabaya, a vocational high school that offers various vocational-based majors. This study uses a quantitative approach with an explanatory design, which aims to test the causal relationship between the variables studied. Data were collected through a survey using a closed questionnaire instrument that has gone through a validity and reliability test process. The number of respondents in this study was 105 students, selected through a proportional random sampling method based on the number of students from each existing major. The data analysis technique used was multiple linear regression with the help of statistical software. The results of the study indicate that simultaneously, both hard skills and soft skills have a significant influence on students' work readiness. This work readiness was measured based on students' perceptions of their abilities to face the world of work, including readiness for job interviews, teamwork, problem-solving, and time management. However, when tested partially, only soft skills had a significant influence on students' work readiness. Hard skills, while important, did not show a significant effect separately. These findings confirm that the development of non-technical skills such as effective communication, work ethic, responsibility, and team collaboration should be an integral part of the vocational education curriculum.